P494 Impact of early optimization of ustekinumab on mid-term targets in severe Crohn's disease: THE MUST study. (30th January 2023) - Abdelmoula, A; Chateau, T; Hupe, M; Boschetti, G; Roblin, X; Nancey, S; Mathieu, N
Abstract: Background: As a substantial proportion of patients with Crohn's disease (CD) experiences a refractory disease course, immediate drug intensification may be an option to optimize the effectiveness of current biotherapies. Aim : to compare the one-year efficacy of immediate dose escalation of ustekinumab 90 mg to 4-weekly with that of 8-weekly dosing after intravenous (iv) induction in severe active CD patients. Methods: The MUST (meta-optimization of Ustekinumab) study is a real-life multicenter observational French retrospective cohort study including patients with severe active CD. All patients from three academic IBD centers who received induction therapy with IV ustekinumab followed with subcutaneous (sc) UST 90 mg, either 4-weekly (MUST group) or 8-weekly (STD group) were included from Jan 2019 to Dec 2020. The choice of treatment regimen was left at the physician's discretion. Severe active CD was defined by HBI > 16 and stool frequency (SF) ≥ 4 and abdominal pain (AP) ≥ 2 over one week and at least one objective evidence of inflammation (CRP ≥ 5 mg/L and/or FCal ≥ 250 μg/g and/or radiologic and/or endoscopic signs of disease activity). The primary endpoint was PRO-2 based clinical remission defined by SF≤2-8 and AP ≤1, and either FCal <250 μg/g and/or CRP <5 mg/L at week 52. Key secondary endpoints were PRO-2 remission, endoscopic improvement and steroid-free clinical remission at week 52. Results: 203 adult patients were included, either in the MUST group (n = 59) or in the STD group (n = 144). Baseline patient demographics and disease characteristics were similar between groups. Median disease duration was 9 years (IQR: 5 – 14 yrs), 66% were females. Disease location according to the Montreal classification was L1 and L3 in 36% and 44 % of patients. All had previously been exposed to more than one biotherapy, 27% experienced perianal CD, and 35% had undergone previous CD-related surgery. At week 52, the adjusted difference between the two groups for the primary endpoint was 15.8% (95% confidence interval (CI) 0.21 – 0.94; p = 0.029) with significantly higher clinical remission in the MUST group. The adjusted difference for PRO-2 remission was 3.7% (CI 0.45 - 1.66; p = 0.64). All patients, except one in the STD group, were weaned off steroids at week 52. Endoscopic improvement was similar in both groups (61.9% vs. 61.5%, p=0.98). Adverse events were not significantly different in both arms (42.4% vs 34.7%, p=0.338). Conclusion: In the treat-to-target era, our real-life study shows that immediate escalation of ustekinumab therapy to 4-weekly dosing could achieve higher clinical remission at one year than 8-weekly dosing in severe CD. These findings should be confirmed in a dedicated prospective randomized trial.